Real-time multimedia standards in DQDB - Santos, Rodrigo Martin (2000)
In the present work, the necessary and sufficient conditions for the real-time schedulability of Dual Queue Dual Bus (DQDB) networks are formally proved, strictly adhering to the letter of the standard as it stands today. With those results, the quality of the standardized multimedia applications that a given DQDB network can carry is analysed.